2021
DOI: 10.1530/ec-21-0086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma glucose at admission on COVID-19 mortality: experience from a tertiary hospital

Abstract: Objective: Plasma glucose has been correlated with in-hospital mortality among many diseases including infections. We aimed to study plasma glucose at admission of hospitalized patients with COVID-19 at a tertiary care referral hospital at Jodhpur, India and its relation with mortality. Design: A hospital-based clinical study of plasma glucose of COVID-19 patients conducted from May 15th to June 30th, 2020 after ethical approval. Measurements: Random blood samples at admission were collected for plasma gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…We conducted this meta-analysis on overall 31 909 COVID-19 patients from 147 studies. 2 , 4 - 7 , 9 - 18 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…We conducted this meta-analysis on overall 31 909 COVID-19 patients from 147 studies. 2 , 4 - 7 , 9 - 18 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…The compromised innate immunity, an underlying chronic low-grade inflammation and an exaggerated pro-inflammatory response, characterized by increased cytokines like IL-1, IL-6, TNF-α, C-reactive protein, ferritin, and a hypercoagulable state contribute to the increasing severity in diabetics [ [9] , [10] , [11] ]. Acute hyperglycemia can upregulate angiotensin-converting enzyme 2 (ACE-2) expression facilitating viral entry, while chronic hyperglycemia can lead to low ACE-2 expression, leading to decreased degradation of angiotensin II to the vasodilatory, anti-proliferative and anti-inflammatory peptide angiotensin [ [1] , [2] , [3] , [4] , [5] , [6] , [7] ]. This response may be exaggerated after the immune response after natural infection or vaccination [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in multiple studies that diabetes has been associated with increased risk of severe disease, acute respiratory distress syndrome (ARDS), disease progression and increased mortality rates [ 3 , 4 ]. In fact, there exists a bidirectional relationship between SARS-CoV2 infection and diabetes, with infection being associated with worsening of hyperglycemia in preexisting diabetes and new-onset hyperglycemia [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study reported a three times higher mortality in patients with diabetes as compared with those without diabetes. [ 9 ] A systematic review conducted by Almeida-Pititto et al . [ 10 ] demonstrated increased severity and higher mortality in patients with diabetes as compared with patients without diabetes.…”
Section: Introductionmentioning
confidence: 99%